Polyphenols and antioxidant capacity of ethanolic extract of flowers of Annona muricata L. (Guanábana) - Delgado C., Sonia M. (2021)
The properties of Annona muricata L. (guanabana) have been demonstrated in studies carried out on the its leaves, pulp, seeds, stems and fruit peel; highlighting in each of them its antioxidant properties. In the present work the quantification of the total polyphenols and the evaluation of the antioxidant capacity in the ethanolic extract of the flowers of Annona muricata L. (guanabana) was carried out. The flowers samples were collected in the province of Jaen (Cajamarca, Peru). The ethanolic extract was obtained by maceration of the pulverized dried flowers. The quantification of the polyphenols in the ethanolic extract of the flowers was carried out using the Folin-Ciocalteu technique using gallic acid as a pattern. The evaluation of the antioxidant capacity was carried out using the methods of capturing the radical’s DPPH and ABTS. + using the Trolox as a pattern for both methods. The total polyphenols obtained in the ethanolic extract was 10,946 ± 0,008 mg GAE/g. The IC50 values were 104,28 µg / mL for the DPPH stem and 73,22 µg / mL for the ABTS. +. According to the results obtained from the ethanolic extract of the flowers of Annona muricata L., it has an important antioxidant activity, being greater in its neutralizing capacity on the radical ABTS. +.